Overview of searchable encryption research - Ying LI; Chunguang MA (网络与信息安全学报)
With the development of cloud computing,there is an increasing number of companies and individuals outsourcing their data to cloud server in the encrypted form to protect data security and user privacy.As a result,efficient retrieval of encrypted data stored on cloud server has become the issue that users may pay attention to.Searchable encryption (SE) is a cryptographic primitive that supports keyword search over encrypted data,and migrates the cumbersome search operation to the cloud server to utilize its vast computational resources.Reviews previous research according to the different cryptosystems used,and divides SE into two groups,that is symmetric searchable encryption and asymmetric searchable encryption.Based on this classification,first introduces a typical program,and then introduces from the two aspects of the expression of searchable encryption and security.Finally,the need-to-be-solved problems and main research directions are discussed.